A patient-centered interactive voice response system for supporting self-management in kidney transplantation: design and field testing - Raheleh Ganjali; Raheleh Ganjali; Mahin Ghorban Sabbagh; Mahin Ghorban Sabbagh; Saeid Eslami; Saeid Eslami (Frontiers in Digital Health)
IntroductionSelf-management is the ability to control one's own responses to treatments, physical and psychological side effects, and lifestyle choices related to a chronic condition.PurposeTo describe the development of a standard and practical user-centered design process for an interactive voice response system (IVRS) to improve self-management in kidney transplant (KT) recipients.MethodsThe IVRS was constructed utilizing the four phases of the Center for eHealth and Wellbeing Research (CeHRes) roadmap: the contextual inquiry, the value specification, the design phase, and evaluation. First, a literature review, background analysis, and needs assessment were used to identify the needs and problems and solutions related to self-management of KT recipients. Then, with the help of a team of experts and KT recipients, a logic model was created and evaluated. The IVRS was developed through iterative design development in response to these findings. Finally, fifteen end users (KT beneficiaries and health professionals) participated in a usability field test by completing a thinking -aloud test and a questionnaire based on the System Usability Scale (SUS).ResultsThe review study indicates the necessary of self-management education and the potential outcomes and functionalities of information technology intervention. The situation analysis and needs assessment led to the final important requirements for the design of the intervention. All values were identified in three meetings with principal stakeholders, and a logic model was designed. The user test yielded an average SUS score of 81.2, and these results served as the basis for the usability requirements. Health Care Providers (HCPs) struggled with storing the profile of registered patients, setting up medication and personalizing adherence calls, and educational calls and follow-ups.ConclusionFollowing the CeHRes roadmap, an intervention based on IVRS was developed with considering the needs and preferences of KT recipients and HCPs. Designers and researchers could use the CeHRes roadmap as a reference when developing IT-based intervention systems. However, decisions must be made about the thoroughness of the execution of each phase, taking into account time constraints.